PENGARUH DANA PIHAK KETIGA, KECUKUPAN MODAL, TINGKAT PENGEMBALIAN, DAN KREDIT BERMASALAH TERHADAP PERTUMBUHAN KREDIT DAN KONSEKUENSINYA TERHADAP RASIO HARGA PASAR SAHAM PADA BANK YANG GO PUBLIC DI INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study is a study that examines the effect of third party funds, Capital Adequacy Ratio, Return On Asset, and Non Performing Loans on Loan Growth and its consequences to Price Book Value on go public banks in Indonesia.The study population was banking companies listed in Indonesia Stock Exchange. While the sample is determined by purposive sampling method is the method of collecting the sample members based on certain criteria considerations. The criteria used is a banking company that is listed on the Indonesia Stock Exchange, with the period between the years of 2008-2011 Financial Statements, the company which does not have complete data and has a negative net income excluded from the sample in order to obtain 116 samples of research.The results showed that the Third party funds significant negative effect on the loan growth, CAR positive and significant impact on loan growth , ROA positive and significant effect on loan growth, and NPLs a significant negative effect on the loan growth, loan growth positive and significant effect on the PBV.Keywords: Third party funds, CAR, ROA, NPL, Loan Growth, & PBV